KARAKTERISTIK FISIK DAN KIMIA FLAKES TEPUNG KELOPAK JANTUNG PISANG KEPOK KUNING (Musa paradisiaca Linn) - Ariska Rafi Tri Yaningsih; Safinta Nurindra Rahmadhia (AGROINTEK, 2023)
Kepok yellow banana blossom (JPKK) is one type of banana blossom that is usually consumed by the public. JPKK has high fiber content and low fat. Flakes are ready to eat  foods that are consumed as a substitute for breakfast. The aim of this study was to determine the chemical  and physical characteristics of JPKK petals flour flakes. The comparison of JPKK petal flour and wheat flour in the formula for making flakes consists of 0g:100g; 25g:75g; and 50g:50g. Flakes will be analyzed chemically and physically, including moisture content, ash content, total protein content, fat content, crude fiber content, carbohydrate content by different, hardness, and swelling power. The results of this study indicate that the chemical characteristics of JPKK petal flour flakes by testing water content between 2.70-3.71%, ash content between 1.72-4.63%, total protein content between 5.78-7.51%, fat content is between 4.32-5.58%, carbohydrate content by different is between 79.98-84.22%, and crude fiber content is 4.52-10.15%. The physical characteristics of JPPK petal flour flakes have a hardness level between 12.07-13.79N and a swelling power between 4.8-6.57g/g. The addition of JPKK petal flour affects the chemical and physical properties of JPKK flakes, so that it can increase protein content, crude fiber content, reduce fat content, carbohydrate content, hardness, and swelling power. The best formulation of JPKK petal flour flakes was at F3 with a ratio of JPKK petal flour 50g and wheat flour 50g.